2021
DOI: 10.1016/j.adaj.2021.02.013
|View full text |Cite
|
Sign up to set email alerts
|

A clinical investigation of dental evacuation systems in reducing aerosols

Abstract: Background The route of transmission of severe acute respiratory syndrome coronavirus 2 has challenged dentistry to improve the safety for patients and the dental team during various treatment procedures. The purpose of this study was to evaluate and compare the effectiveness of dental evacuation systems in reducing aerosols during oral prophylactic procedures in a large clinical setting. Methods This was a single-center, controlled clinical trial using a split-mouth de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
10
0
2
Order By: Relevance
“…Avoiding the recycling of unfiltered air is very important mainly in healthcare-related installations as the airborne transmission of the virus is possible, as mentioned above [14,15,23,24]. In a recent study, it was shown that the combination of the intraoral and extraoral mechanical suction of the produced aerosol had better results in reducing the microbial load in the air than the use of intraoral alone [25]. The same conclusions arose in a very recent article stating that even portable high-efficiency particulate filters may be installed especially in an old-fashioned ward in healthcare institutions with suboptimal ventilation [13].…”
Section: Overall Monitoringmentioning
confidence: 99%
“…Avoiding the recycling of unfiltered air is very important mainly in healthcare-related installations as the airborne transmission of the virus is possible, as mentioned above [14,15,23,24]. In a recent study, it was shown that the combination of the intraoral and extraoral mechanical suction of the produced aerosol had better results in reducing the microbial load in the air than the use of intraoral alone [25]. The same conclusions arose in a very recent article stating that even portable high-efficiency particulate filters may be installed especially in an old-fashioned ward in healthcare institutions with suboptimal ventilation [13].…”
Section: Overall Monitoringmentioning
confidence: 99%
“…In the absence of a ‘gold standard’ for measurements, and the absence of an ‘acceptable threshold’ of aerosol, measuring aerosol mitigation remains challenging. Many studies have evaluated aerosol mitigation using extra-oral high-volume suction devices, [ 7 , 10 , 15 , 16 , 19 ]. In some settings, these devices show effective aerosol removal but these devices are not widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of HVE available are HVE that is attached directly to the dental unit and portable HVE that is not installed in the dental unit. The HVE that is installed directly on the dental unit utilizes the suction system of the dental unit integrated with the drain line (12,27). This HVE uses a cannula that looks like a small funnel attached to the suction and can be positioned directly close to the tooth being treated.…”
Section: Discussionmentioning
confidence: 99%
“…This HVE uses a cannula that looks like a small funnel attached to the suction and can be positioned directly close to the tooth being treated. The use of HVE makes the aerosol generated in the process of action can be directly sucked in large volumes (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation